Development of a model care pathway for adults undergoing colorectal cancer surgery: Evidence‐based key interventions and indicators. Issue 1 (1st February 2017) - van Zelm, Ruben; Janssen, Ingrid; Vanhaecht, Kris; de Buck van Overstraeten, Anthony; Panella, Massimiliano; Sermeus, Walter; Coeckelberghs, Ellen
Abstract: Rationale, aims, and objectives: During the last decades, perioperative care for patients with colorectal cancer has shifted towards more standardized care, so‐called "enhanced recovery after surgery." Those programs aim to optimize interventions in perioperative care to decrease the rate of postoperative complications, improve patients' recovery, and shorten hospital stay. The purpose of this literature review is to identify, summarize, and operationalize the clinical content of both key interventions and clinical indicators to develop an evidence‐based model pathway for surgical patients with colorectal cancer. Methods: A systematic search in 3 databases was conducted to identify key interventions (KIs) and indicators to measure the effect of implementation of care pathways. The KIs from the enhanced recovery after surgery protocol were listed and used as framework to identify and match KIs used in the included studies. The Clinical Pathway Compass was used to categorize the indicators. Results: Fifteen studies were included. The number of KI used in the study protocols ranged from 9 to 20. In total, 33 KIs were identified. Little information was available concerning the implementation of and compliance to the protocol. Length of stay and complication rate are the most common used indicators (used in 15/15 and 14/15 of the studies), followed by 21 other measures. All but one of the included studies reported a reduction in length of stay. Conclusion: There is a considerable variation in both number of KIs and indicators as well as operationalization of key interventions, for surgical patients with colorectal cancer documented in literature. Therefore, we summarized the input from different studies and developed an evidence‐based model pathway, which can serve as a basis for a local/regional care pathway team to build their own pathway.